Understanding Emigration Policy Variation in Authoritarian Regimes: How Pillars of Stability and Regime Type Shape Authoritarian Exit Controls - Sitaula, Suyasha (Auckland University of Technology, 2025)
Why do some authoritarian regimes restrict the exit of their citizens while others do not? Drawing on a comprehensive quantitative analysis of authoritarian regimes from 1946–2010, I argue that this variation in authoritarian emigration policy can be systematically shaped by regime type and stability mechanisms. Employing Gerschewski’s three pillars of authoritarian stability—repression, legitimation, and co-optation as a theoretical framework, I investigate how reliance on each pillar can influence the permissiveness or restrictiveness of authoritarian emigration policy. Additionally, I analyse whether personalist regimes implement more restrictive emigration controls than nonpersonalist authoritarian regimes. The findings reveal significant patterns: regimes that heavily rely on repression systematically implement more restrictive emigration policies, while those emphasising co-optation tend to adopt more permissive approaches. The analysis also suggests that legitimation may have more complex, non linear implications for emigration policies than hypothesised, warranting further investigation. Meanwhile, when operationalised through measure of power concentration in a single leader, personalist regimes demonstrate a strong tendency toward restrictive emigration policies. To examine these statistical relationships and explore possible causal mechanisms, I also present diverse illustrative cases of the Dominican Republic, Kyrgyzstan, Mozambique, Singapore, and North Korea. These cases provide contextual evidence supporting the quantitative findings while illuminating the strategic calculations that shape authoritarian emigration policies across different regional and historical contexts. Overall, this thesis contributes to a more nuanced understanding of how authoritarian regimes vary in their control over citizens’ freedom of movement and how deeper structural and institutional features shape such variation.